(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The article attempts to investigate the specificity of the novel «Look Into My Dreams» by moder Ukrainian writer Max Kidruk, which is irrational in the art model of the world. Considerable attention is paid to the characterization of the onyric space of the work. In the article we traced: the specialities of the artistic reproduction of the physiological transformations of the characters, the correlation of «oneʼs own» and «another’s» in the mind of a person are traced; psychological states and processes.